The Role Of Technology In English Curriculum Design - Devi Hanas Tasya; Siminto (BADAN PENERBIT STIEPARI PRESS, 2023)
The curriculum needs to be deliberately organized and structured into specific programs in order to meet the country's educational objectives established by the Indonesian government. What should be included in an educational program is decided in large part by the use of technology in the curriculum. Research studies that look at the degree and efficiency of technology integration in Indonesia's English curriculum are required. As a result, it's critical for educators to research efficient methods for incorporating technology into the creation of English curriculum and to keep up with the most recent advancements in technology that can enhance language learning. The main research methodology used in this work is research library, which entails a thorough examination of pertinent books, articles, and research papers. The aim of this article is to examine how technology has affected the design of the English curriculum and how it may be applied to improve language instruction in Indonesia.